Proposição de esquema conceitual para a governança de redes de cooperação federadas - Roth, Ana Lúcia (Universidade do Vale do Rio dos Sinos, 2011)
This study concerns Federated Cooperative Networks governance, a specific Interorganizational Relationship (IOR) typology. Motivated by a theoretical gap in this subject, we sought to identify the elements forming the Federated Cooperative Networks governance system and how they can be designed to reduce conflicts and agency costs in Federations. It was noticed that studies describing and analyzing internal IORs governance elements do not approach separation of ownership from control, characteristic of Federated Cooperative Networks. Authors who discuss separation of ownership from control don’t show the internal elements of IOR governance. And the studies don’t discuss how the internal governance elements (governance structure and mechanisms) might be combined to minimize conflicts and agency costs either. Based on the Agency Theory, Representation Theory and Organizational Theory employed in IORs context, we have proposed three elements for the Federated Cooperative Networks governance system: (a) a governance structure; (b) governance mechanisms instituted to encourage and control the behavior of agents; (c) governance mechanisms instituted to encourage and control the behavior of principals. For the empirical validation of these elements, we have chosen to perform a qualitative study, of exploratory nature, through the multiple case study method. The study was operated through two case studies: one at Rede Âncora Brasil and the other at Rede Construir. The results allow us to assert that, although present, structural elements and governance mechanisms over principals and agents show distinct features. On one extreme, there is a Federation with a higher level of decision instances, a higher number of activities developed by the Federation, which tend to lead to more centralization, formalization, standardization, coordination and control. On the other extreme, a Federation with little decision instances, and a lower number of activities developed by the Federation, which tend to lead to decentralization, less formalization, standardization, coordination and control. The empirical study added the element representation and participation in the Federated Cooperative Networks governance structure. The internal and external governance mechanisms, widely employed in corporations, were also identified in the Federated Cooperative Networks context. However, we have found that the Administrative Council, or corresponding agency, is the most effective mechanism in reducing agency costs and conflicts. Among the theoretical contributions of the study, adopting a new perspective in the concept of Federated Cooperative Networks governance under the light of the Agency theory can be stressed.
Keywords: Governança; Relações interorganizacionais; Redes de cooperação; Empreendimentos coletivos; Federação; Governance; Interorganizational relationship; Cooperative networks; Federation; Federated cooperation networks; ACCNPQ::Ciências Sociais Aplicadas::Administração